Respuesta :

Answer: I hope it helps

  1. F
  2. D
  3. H
  4. I

Step-by-step explanation:

[tex]y \alpha x\\y= kx (1)\\Make=k-subject-of-the-formula\\\frac{y}{x} =\frac{kx}{x} \\\\\\[/tex]

[tex]k = \frac{y}{x}. \\when-y =3, x= 7 \\k = \frac{3}{7} \\Put - k- = 3/7 -in eq - 1\\y = 3/7x = F \\[/tex]

[tex](4n+3n^2+2)-(n-6n^2+1)\\4n +3n^2+2-n+6n^2-1\\\\3n^2+6n^2+4n-n+2-1\\9n^2+3n+1[/tex]

y = 2x-4

when x= 0

y = 2(0)-4

y =-4

y = 2x - 4

when x = 1

y = 2(1) -4

y = 2-4

y = 2

and so on....

A - Negative - the more slices eaten , the fewer there are

[tex]f(x)= 2x^2 +x-12\\f(3) = 2(3)^2+3-12\\f(3) = 2*9+3-12\\f(3) = 18+3-12\\f (3) = 9[/tex]

ACCESS MORE